Outreach Research: A liaison between research and extension - Paudel, MN (Agronomy Journal of Nepal, 2013)
How outreach research has been passed through due course of time in Nepal is put forth. A model of linkages of outreach research in relation to technology dissemination as a liaison between research and extension in the Nepalese context has been shown in a broad perspective. Similarly, how technology is delivered from research station to farmers' fled in a participatory approach involving public-private-partnership through research-extension interphase is mentioned. Also, the relation of outreach research with extension from district to central level is illustrated. There is clear message that why technology generation do not tailor with the demand of client and every concerned institute should dare to accept pros and cons of agro-technology cycle to enhance agriculture and productivity to meet the food security of Nepalese people. This paper explains the limitation and opportunities of agriculture research and development which are not getting priority in a way these should be considered to take pace with present day demand. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 97-108 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9011